A study of the prevalence of diabetes, insulin resistance, lipid abnormalities, and cardiovascular risk factors in patients with chronic plaque psoriasis - Rickson R Pereira; Sangeeta T Amladi; Prema K Varthakavi (Wolters Kluwer Medknow Publications, 2011)
Background: The association between psoriasis, diabetes, and cardiovascular disease remains largely unelucidated in the Indian population. Aims: To study the prevalence of diabetes, insulin resistance, lipid abnormalities, and cardiovascular risk factors in patients with chronic plaque psoriasis. Materials and Methods: Seventy-seven patients of chronic plaque psoriasis and ninety two age- and sex-matched controls were enrolled in the study over a period of one year. Clinical and biometric data were noted and fasting venous blood samples were collected. Nondiabetic patients were subjected to an oral glucose tolerance test with 75 g glucose and postprandial venous blood samples collected at 120 mins. The fasting glucose, insulin, lipid levels, postprandial glucose and postprandial insulin levels were measured in samples from nondiabetic patients whereas fasting lipid levels only were measured in diabetic patients. Results: The prevalence of impaired fasting glucose, impaired glucose tolerance, and diabetes mellitus in psoriatics was 5.2%, 9.1%, and 32.5%, respectively, as compared to 6.5%, 3.3%, and 15.2%, respectively, in the controls. The difference was statistically significant. The odds ratio of having an abnormal glucose metabolism in psoriasis was 2.63. Smoking had a positive association with insulin resistance in psoriatic cases. The serum cholesterol levels were elevated in 29 (37.7%) cases with a mean of 186.27 ± 43.18 and 34 (37%) controls with a mean of 194.38 ± 57.20. The serum HDL-cholesterol levels were reduced in 50 (64.9%) cases with a mean of 53.29 ± 15.90 as compared to 71 (74.7%) in controls with a mean of 48.76 ± 12.85. The serum LDL-cholesterol levels were elevated in 38 (49.4%) cases with a mean of 102.56 ± 44.02 and 36 controls with a mean of 115.62 ± 54.37. The serum triglyceride levels were elevated in 25 (32.5%) cases with a mean of 129.99 ± 61.32 and 38 (41.3%) controls with a mean of 141.04 ± 80.10. The differences between the two groups were not statistically significant. The two groups did not differ with respect to other cardiovascular risk factors such as increased body mass index, increased waist size, increased waist-to-hip ratio, and hypertension. Conclusion: There is a positive association between insulin resistance and psoriasis. No association between psoriasis and dyslipidemia has been found in this study.